1994
DOI: 10.1190/1.1443645
|View full text |Cite
|
Sign up to set email alerts
|

Elastic‐wave stimulation of oil production: A review of methods and results

Abstract: Numerous observations accumulated principally during the last 40 years show that seismic waves generated from earthquakes and cultural noise may alter water and oil production. In some cases wave excitation may appreciably increase the mobility of fluids. The effect of elastic waves on the permeability of saturated rock has been confirmed in numerous laboratory experiments. Two related applications have arisen from these findings. In the first application, high-power ultrasonic waves are applied for downhole c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
182
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(186 citation statements)
references
References 22 publications
2
182
0
2
Order By: Relevance
“…Since the concept of dynamic permeability was proposed several years ago [1,2], it has been extensively used in the study of practical problems such as petroleum recovery [3], soil-ground water transport [4], fluids flowing in porous media [5,6], acoustic waves in porous media [7], wave propagation in foams [8], fluid circulation in biological systems [9], etc. The use of the dynamic permeability as originally proposed [1] however, is not quite correct for some of these systems since the fluid does not behave as a Newtonian fluid but shows viscoelastic features.…”
Section: Introductionmentioning
confidence: 99%
“…Since the concept of dynamic permeability was proposed several years ago [1,2], it has been extensively used in the study of practical problems such as petroleum recovery [3], soil-ground water transport [4], fluids flowing in porous media [5,6], acoustic waves in porous media [7], wave propagation in foams [8], fluid circulation in biological systems [9], etc. The use of the dynamic permeability as originally proposed [1] however, is not quite correct for some of these systems since the fluid does not behave as a Newtonian fluid but shows viscoelastic features.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed in some laboratory measurements and field applications that imposing harmonic signals into cores or reservoirs sometimes may induce higher fluid flow rates (Pan and Horne 2000). Further the fact that the pore pressure may undergo variations under the influence of seismic waves is well known to geotechnical engineers (Beresnev and Johnson 1994). In addition, laboratory experiments have shown that ultrasonic radiation can considerably increase the rate of flow of a liquid through a porous medium (Aarts and Ooms 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Biot theoretically studied this phenomenon by considering the flow of a viscous fluid in a tube with longitudinally oscillating walls under an oscillatory pressure gradient. Apart from the fundamental interest, the investigation of the dynamics of fluid in porous media under oscillatory pressure gradient and oscillating pore walls is of prime importance for the recently emerged technology of acoustic stimulation of oil reservoirs [2]. For example, it is known that the natural pressure in an oil reservoir generally yields no more than approximately 10 percent oil recovery.…”
Section: Introductionmentioning
confidence: 99%